Students' Consumerism Attitude to Higher Education Institutions - Raden Johnny Hadi Raharjo; G. Oka Warmana; Damar Kristanto; Anandya Zalva Yunnafisah; Andrew Baihaqi Firdaus (Future Science, 2022)
Modern society argues that society depends on the ideology of consumption. Consumption is not only a marker of the social status of a person or group. Status consumption is a mechanism used by consumers to gain social status or prestige by buying and consuming goods that customers and their significant other consider high status. but also a way of solving problems, constructing meaning for the environment around us, and even forming personal identities. The increasing reach of the ideology of consumerism has expanded the traditional definition of what is called a